Beleaguered Nation : The Making and Unmaking of the Assamese Nationality - Nag, Sajal, (Brill | Manohar Publishers & Distributors, 2017)
The multi-ethnic state of Assam emerged to be a minefield of conflict and violence over assertions of autonomy in the 1980s. While the Assamese leaders were fighting a battle against the Bengali and the fear of immigrant Muslim domination after independence, one by one other tribal groups challenged the hegemony of the Assamese and broke free from the state: the Naga, the Khasi-Jyntia, the Mizo and the Arunachalis. They were followed by the Bodos, Dimasas and the Karbis who despite having got their autonomy are still fighting a fierce battle for complete statehood. There is a growing demand for a Ahom and Kamatapur state as well as from the smaller communities like the Rabhas, Hasong, Tiwa, Mishing, Sonowal Kachari, Thangal Kachari and Deuris, and even domiciled Gorkhas which if conceded would reduce the size of the Assamese nationality and Assamese territory to only a few pockets. There are extremist outfits like the United Liberation Front of Assam which saw secession from India as the solution to the problem of Assamese nationality, others like the Karbi National Volunteers, United Peoples Democratic Solidarity, Dima Haloa Daoga (two factions), Kuki National Front and Kuki National Army, Bodo Security Force, National Democratic Front of Bodoland resorted to violence as a mode of their assertions. Unprecedented turbulence, instability, violence, and internal displacement engulfed the entire region creating a severe crisis for the Indian state. Submerged in this ethnic cauldron, the Assamese were indeed a beleaguered nation fighting for survival amidst such multiple ethnic challenges. This book is about contradictions, conflicts, machinations, subversions, nature of state intervention and the intricate process of making and unmaking of Assamese nationality vis-a-vis north east India.